ANALISA RISIKO ERGONOMI PADA PROSES PEMBUATAN TAHU TRADISIONAL DI KECAMATAN TIRTAYASA - Ika, Novarina; Haki, Ubay (Bussman Journal : Indonesian Journal of Business and Management, 2023)
This study examines ergonomic hazards in the traditional tofu making process in Tanara, Serang Regency, Banten Province, Indonesia. This study was made to determine the level of risk of skeletal muscle disorders that can occur to workers who do manual work in the process of processing soybeans into tofu products. The study used the Quick Exposure Checklist (QEC) method to analyze and provide suggestions for improvements to minimize ergonomic hazards to workers